Experimental and simulation studies of motion control of a Delta robot using a model-based approach. (8th November 2017) - Kuo, Yong-Lin; Huang, Peng-Yu
Robot manipulators are mostly used to complete positioning tasks, and the conventional approach utilizes position-based control scheme, which converts a robot control problems to several motor control problems, where encoder signals are used to fulfill feedback control. This control scheme might not provide excellent positioning accuracy due to the lack of the dynamics of robot manipulators. This article presents a simple model-based control scheme to achieve the positioning control and applies the scheme to a Delta robot, which can perform the motion with three translational degrees of freedom. The proposed scheme first evaluates the applied torques of motors based on robot's kinematics and dynamics using the encoders, and then the evaluated torques are sent to controllers to fulfill feedback control. The entire control loop is little similar to torque control, but torque or current sensors are not used. To demonstrate the performances of the proposed scheme, not only the numerical simulations are performed but also the experimental work is conducted. Both results are compared with those by applying the position-based control. The results show that the proposed model-based control scheme provides better positioning accuracy.